2012
DOI: 10.1002/ajpa.22112
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in body form of prehistoric Jomon males in the Japanese archipelago: Its ecogeographic implications

Abstract: Diversity of human body size and shape is often biogeographically interpreted in association with climatic conditions. According to Bergmann's and Allen's rules, populations in regions with a cold climate are expected to display an overall larger body and smaller/shorter extremities than those in warm/hot environments. In the present study, the skeletal limb size and proportions of prehistoric Jomon hunter-gatherers, who extensively inhabited subarctic to subtropical areas in the ancient Japanese archipelago, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 103 publications
(176 reference statements)
5
43
2
1
Order By: Relevance
“…A southern or northern origin hypothesis of the Jomon people has been discussed on the basis of morphological and genetic studies (Turner, 1987(Turner, , 1989(Turner, , 1990Matsumura and Hudson, 2005;Cavalli-Sforza et al, 1988;Kozintsev, 1990;Omoto and Saitou, 1997;Ishida and Kondo, 1999;Bannai et al, 1999;Tokunaga et al, 2001;Tajima et al, 2004;Tanaka et al, 2004; Komesu et al, 2008;Hanihara and Ishida, 2009;Adachi et al, 2011), but this issue remains unresolved. However, because the long distal segments in the intralimb proportions of the Jomon people are stable from northern Hokkaido to the southern Ryukyu Islands (Fukase et al, 2012), the stability might decrease with the north-south cline of the intralimb proportions in this study. As a last reason, the recent Ryukyu Islanders show very low brachial and crural indices (76.0 and 79.9, respectively), which are comparable to those in northeast Asians.…”
Section: Intra-limb Proportionmentioning
confidence: 58%
See 1 more Smart Citation
“…A southern or northern origin hypothesis of the Jomon people has been discussed on the basis of morphological and genetic studies (Turner, 1987(Turner, , 1989(Turner, , 1990Matsumura and Hudson, 2005;Cavalli-Sforza et al, 1988;Kozintsev, 1990;Omoto and Saitou, 1997;Ishida and Kondo, 1999;Bannai et al, 1999;Tokunaga et al, 2001;Tajima et al, 2004;Tanaka et al, 2004; Komesu et al, 2008;Hanihara and Ishida, 2009;Adachi et al, 2011), but this issue remains unresolved. However, because the long distal segments in the intralimb proportions of the Jomon people are stable from northern Hokkaido to the southern Ryukyu Islands (Fukase et al, 2012), the stability might decrease with the north-south cline of the intralimb proportions in this study. As a last reason, the recent Ryukyu Islanders show very low brachial and crural indices (76.0 and 79.9, respectively), which are comparable to those in northeast Asians.…”
Section: Intra-limb Proportionmentioning
confidence: 58%
“…Although analysis of variance revealed a significant difference between the samples compared in this study, the crural index (T1:F1) was not significantly correlated with latitude, partly because the Jomon and Ainu peoples were included in this study (Figure 2c). The Jomon and Ainu peoples have very high crural indices among the East Asians, while such indices are low in the Yayoi people, modern mainland Japanese, and Ryukyu Islanders from the same Japanese islands (Yamaguchi, 1989;Temple et al, 2008;Fukase et al, 2012). However, even when the Jomon series was excluded from the analysis, the correlation was not significant.…”
Section: Intra-limb Proportionmentioning
confidence: 96%
“…Fukase et al (2012) pointed out the geographical cline of Jomon postcranial metrics, which was recognized as a reflection of Bergmann's law, i.e. a body size difference from north to south in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The lengths of the postcranial long bones and the size of the femoral head can be interpreted as a proxy of the body size (stature and body weight). Fukase et al attributed the observed cline of the body size to 'Bergmann's rule'; however, they did not exclude other factors, such as phylogenetic dissimilarity or ad hoc growth differences among the Jomon population (Fukase et al, 2012).…”
Section: Regional Variation In Jomon Skeletal Remainsmentioning
confidence: 99%
See 1 more Smart Citation